2004
DOI: 10.1142/s0192415x0400251x
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Chemical Changes in Pyrite after Traditional Processing for Use in Medicines

Abstract: Pyrite has been the most commonly used medicinal mineral, and its toxicity was reduced by traditional processing operations including heating and quenching in vinegar. To verify the scientific effects of this process, pyrite was processed at temperatures up to 850 degrees C and through as many as five processing cycles. A metal extraction test was carried out from the processed pyrites on the assumption that pyrite medicines with the lowest toxic metal content would be most desirable. Increasing temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…It can directly harm human brain cells and cause congenital shallow of the cerebral sulcus. Hwang et al 6 found that arsenopyrite did not disappear even aer ve processing cycles at 450 C, but vanished aer only one processing cycle at 650 C, which may be ascribed to the oxidation of arsenic compound at higher temperature and then dissolution in vinegar.…”
Section: Magnetic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can directly harm human brain cells and cause congenital shallow of the cerebral sulcus. Hwang et al 6 found that arsenopyrite did not disappear even aer ve processing cycles at 450 C, but vanished aer only one processing cycle at 650 C, which may be ascribed to the oxidation of arsenic compound at higher temperature and then dissolution in vinegar.…”
Section: Magnetic Characteristicsmentioning
confidence: 99%
“…The surface features of pyrite are changed and toxic elements are reduced aer being calcined and quenched in vinegar. 6 However, previous studies only focused on the changes of mineral phase characteristics of pyrite before and aer processing. To the best of our knowledge, the changes of mineral phase characteristics of processed pyrite, or its effects on osteoblast proliferation and differentiation have never been studied hitherto.…”
Section: Introductionmentioning
confidence: 99%
“…For example, minerals are commonly used in Chinese herbals remedies, and Chinese herbalists believe that the toxicity of minerals can be removed by traditional processing operations, including heating and quenching in vinegar, referred to as “pao zhi” [90]. However, no scientific evidence has shown that toxic contents, such as AA or heavy metals, can be eliminated by these methods.…”
Section: From Observational Studies To Preventive Actionsmentioning
confidence: 99%
“…[ 6 – 8 ] Generally, pyritum is a heavy metal raw material that can be used as a drug through a safe formulation method. [ 9 ] In Korea, there have been many studies on pyritum manufacturing technology or animal experiments, but it was not easy to find relevant clinical literature. [ 2 , 3 , 10 ] Pyritum was used clinically in China through Chinese patented medicine (CPM) containing pyritum or decoction with other herbal materials rather than alone in clinical practice.…”
Section: Introductionmentioning
confidence: 99%